Performance measures for endoscopy services: A European Society of Gastrointestinal Endoscopy (ESGE) quality improvement initiative - Valori, Roland (United European Gastroenterol J, 2018)
The European Society of Gastrointestinal Endoscopy (ESGE) and United European Gastroenterology present a list of key performance measures for endoscopy services. We recommend that these performance measures be adopted by all endoscopy services across Europe. The measures include those related to the leadership, organization, and delivery of the service, as well as those associated with the patient journey. Each measure includes a recommendation for a minimum and target standard for endoscopy services to achieve. We recommend that all stakeholders in endoscopy take note of these ESGE endoscopy services performance measures to accelerate their adoption and implementation. Stakeholders include patients and their advocacy groups; service leaders; staff, including endoscopists; professional societies; payers; and regulators.